(untitled) (DARYAFT, 2023)
The purpose of this article is to analyze Chaudhry Afzal’s autobiography "MeraAfsana" in the colonial context. We have seen how the colonial system and its inhabitants were able to establish and rule their colonies in India. Neocolonialism is a system in which powerful nations take control of weaker nations. By using the resources of the subjugated nation to increase their economic and statistical efficiency, they continue to strengthen themselves. This makes the economy of the settlers stronger. When a country occupies another country through its military power, it is the beginning of the formation of the colonial system. In the world where this new population is established, the occupiers impose their laws, social system and government on the local inhabitants. Western colonialism in the form of colonies, gradually set foot in the subcontinent and then they looted the wealth and capital of this colonies. Choudhary Afzal Haq was among those who expressed the response to colonialism in that period. He was put in jail several times for the freedom movement. This article explains the services that he played in awakening the consciousness among the Muslims and strengthening their political movements, which weakened the roots of the colonial system and benefited the people of India. Choudhary Afzal has drawn a beautiful map of the racial superiority of the West, exploitation of resources, oppression and violation of human rights in his autobiography.